PARTNERSHIP MODEL FOR OPTIMIZING THE USE OF VILLAGE FUNDS - Mukhtar Sarman (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2018)
Since 2015, the Government has allocated village development funds in theform of Village Fund policies of IDR 20.7 trillion, then in 2016 it increased to IDR46.9 trillion, and continues to increase in the following years. However, based on fieldresearch in a number of regions in Indonesia, it turns out that the use of Village Fundsis not optimal, some of which have been proven wrongly targeted, not transparent inuse, and not accountable in reporting. The aspect of planning activities and the qualityof human resources implementing policies and coordination between parties thatshould play a role are still a major problem.The PPP (Public-Private Partnership) model is actually intended for thedevelopment of large-scale projects, such as the construction of highways or seaportsand airports. But by taking the substance of cooperation from the parties that eachhave strengths, the PPP model (and its variants) may be applicable in the use ofVillage Funds. Using secondary data analysts, the following article discusses thetheoretical aspects of the advantages of the PPP model. This model is juxtaposed withcases of success in building the economic self-reliance of rural communities with thehelp of private parties and academics. It is assumed that the partnership model can bean alternative solution to further optimize the use of Village Funds in order to reducepoverty in rural areas.